Secondary School Education in Nigeria: Problems, Prospects and Solutions - Abershi Japhet Zhenseh; Mikky Wunubo Gani; Ogunode N. J. (International Journal on Integrated Education, 2022)
The quality of public secondary education in Nigeria is falling. This is as a result of numerous problems facing the public secondary schools in Nigeria. This study discusses the problems hindering the development of public secondary schools in Nigeria. The paper used both qualitative and quantitative data to provide empirical support on various points raised. The paper identified inadequate funding, shortage of teachers, inadequate infrastructural facilities, insecurity problem, corruption, poor supervision, over-population, inadequate instructional materials, and politicization of appointment of persons into Education Boards and Commissions and weak administrators. Based on the problems identified, the paper among other recommendation suggested to the federal and states government to increase the funding of the public secondary schools across the country.